Changes in weed flora of basket willow (Salix viminalis L.) under different soil nutrient supply - Szabó, Miklós; Szabó, Béla; Bányácski, Sándor; Simon, László (Acta Agraria Debreceniensis, 2010)
The world is in a continuous progress, as a result of which energy consumption and with this the release of gases with adverse impact show rapid increase. As a result of the survey conducted by the International Energy Agency, if the major economic powers do not initiate a change in their energy policy, the increase of energy consumption may as well reach 40 % by 2030. This increased energy demand is getting more and more difficult to fulfill with the fossil energy resources, which is to lead to an increasing significance of renewable energy resources. In Hungary, these energy resources are the best to provide with biomass growth. Biomass growth for energetic purpose can mostly be provided by energy plants, out of which “energy willow” (Salix viminalis L.) is outstanding with its high yield and with its excellent burning technology characteristics of its timber. The willow’s cropping technology is being established in our country. One of our tasks is to work out an adequate weed control plan. The professional and safe use of herbicides can increase the success of production. In our paper, we discuss the weed flora data collected on treatments applied in the different fertilizer and compost. We started our survey in 2010. We examined twelve different fertilizer and compost treated areas. The dominant weeds were: Amaranthus retroflexus, Chenopodium album, Echinochloa crus-galli among annuals; Cirsium arvense and Agropyron repens among the perennials.